Efficacy and Safety of Granulocyte-Colony Stimulating Factor Therapy in Chagas Cardiomyopathy: A Phase II Double-Blind, Randomized, Placebo-Controlled Clinical Trial - Macedo, Carolina T.; Larocca, Ticiana F.; Noya-Rabelo, Márcia; Aras, Roque; Macedo, Cristiano R. B.; Moreira, Moisés I.; Caldas, Alessandra C.; Torreão, Jorge A.; Monsão, Victor M. A.; Souza, Clarissa L. M.; Vasconcelos, Juliana F.; Bezerra, Milena R.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aim: Previous studies showed that granulocyte-colony stimulating factor (G-CSF) improved heart function in a mice model of Chronic Chagas Cardiomyopathy (CCC). Herein, we report the interim results of the safety and efficacy of G-CSF therapy versus placebo in adults with Chagas cardiomyopathy. Methods: Patients with CCC, New York Heart Association (NYHA) functional class II to IV and left ventricular ejection fraction (LVEF) 50% or below were included. A randomization list using blocks of 2 and 4 and an allocation rate of 1:1 was generated by R software which was stratified by functional class. Double blinding was done to both arms and assessors were masked to allo-cations. All patients received standard heart failure treatment for 2 months before 1:1 randomi-zation to either the G-CSF (10 mcg/kg/day subcutaneously) or placebo group (1 mL of 0.9% sa-line subcutaneously). The primary endpoint was either maintenance or improvement of NYHA class from baseline to 6-12 months after treatment, and intention-to-treat analysis was used. Results: We screened 535 patients with CCC in Salvador, Brazil, of whom 37 were randomized. Overall, baseline characteristics were well balanced between groups. Most patients had NYHA class II heart failure (86.4%); low mean LVEF was 32 ± 7% in the G-CSF group and 33 ± 10% in the placebo group. Frequency of primary endpoint was 78% (95% CI 0·60-0·97) vs. 66% (95% CI 0.40-0.86), p = 0.47, at 6 months and 68% (95% CI 0.43-0.87) vs. 72% (95% CI 0.46-0.90), p = 0.80, at 12 months in placebo and G-CSF groups, respectively. G-CSF treatment was safe, without any related serious adverse events. There was no difference in mortality between both arms, with five deaths (18.5%) in treatment versus four (12.5%) in placebo arm. Exploratory analysis demonstrated that the maximum rate of oxygen consumption during exercise (VO2 max) showed an improving trend in the G-CSF group. Conclusions: G-CSF therapy was safe and well tolerated in 12 months of follow up. Despite of prevention of symptom progression could not be demonstrated in the present study, our results support further investigation of G-CSF therapy in Chagas cardiomyopathy patients. Clinical Trial Registration: www.ClinicalTrials.gov, identifier: NCT02154269.